Cities on the move 7. - Ban, Shigeru; Cook, Peter; Hou, Hanru; Jaukkuri, Maaretta; Obrist, Hans-Ulrich; Sassen, Saskia (Helsinki : KIASMA Museum of Contemporary Art, 1999)
AAGDG93 (Architectural Association Graduate Design Group) ; Andreu, Paul ; Arahmaiani ; Araki, Nobuyoshi ; Ban, Shigeru ; Bunnag, Duangrit ; Büro Friedrich ; Cai Guo-Qiang ; Cáven, Kari ; Chang, Yung Ho ; Chen Zhen ; Chen, Shaoxiong ; Cheung, Amy ; Chi, Ti-Nan ; Choi, Jeong Hwa ; Cook, Peter ; D'Heilly, David ; Dono, Heri ; Draisma, Janica ; Edge ; Findlay, Kathryn ; Foreign Office ; Frémy, Anne ; Fuksas, Massimiliano ; Gatton, Matt ; Geng Jianyi ; Gill, Simryn ; Girard, Greg ; Gonzalez-Foerster, Dominique ; Grou, Christian ; Guan Bee, Tang ; Hanayo ; Hasegawa, Itsuko ; Heiskanen, Outi ; Herzog, Jacques ; Ho Siu-kee ; Ho, Oscar ; Ho, Richard ; Ho, Tao ; Homma, Takashi ; Horelli, Laura ; Huang Yong Ping ; Huang, Chin-Ho ; Isozaki, Arata ; Ito, Toyo ; Jodogne, Lucas ; Jumsai, Sumet ; Kasemkitvatana, Chitti ; Kay, Ngee Tan ; Khoo, Eric ; Kikutake, Kiyonori ; Kim, Jinai ; Kim, Soo-Ja ; Kim, Yun-Tae ; Kitano, Takeshi ; Klopf, Karl Heinz ; Konrad, Aglaia ; Koo Jeong-a ; Koolhaas, Rem ; Korkeila, Jukka ; Kurokawa, Kisho ; Kusolwong Surasi ; Lee, Bul ; Liang, Ju Hui ; Liew, Kung Yu ; Lim, William ; Lin, Yilin ; Linke, Armin ; Liu, Thai Ker ; Lum, Ken ; Lynn, Greg ; Maki, Fumihiko ; Manik, Andar ; Meadows, Fiona ; de Meuron, Pierre ; Minn, Sohn Joo ; Miyamoto, Ryuji ; Molacek, Rudi ; Nantois, Frédéric ; Ngui, Matthew ; Ota, Kayoko ; Ozawa Tsuyoshi ; Pau, Ellen ; Piano, Renzo ; Prawoto, Eko ; Price, Cedric ; Rawanchaikul, Navin ; Reiser, Jesse ; Seijima, Kazuyo ; Seung, H-Sang ; Shen Yuan ; Shi Yong ; Sibayan, Judy Freya ; Sirait, Marintan ; Snellman, tapio ; Snyder, Sean ; Sone Yutaka ; Song Dong ; Spiluttini, Margherita ; Sriwanichpoom, Manit ; Superflex ; Sze, Sarah ; Tan, Aaron ; Tan, Fiona ; Tanaka, Takahiro ; Tay, Kheng Soon ; Thenuwara, Chandraguptha ; etc.
biog. p. 124-177
Cities on the move 7, KIASMA (Museum of Contemporary Art) Helsinki, 06.11.1999 - 09.01.2000. Before coming to Kiasma, this exhibition has been seen at the original launch venues of the project - the Secession in Vienna (26.11.1997 t/m 08.01.1998), the Musée d'art contemporaine, in Bordeaux (04.06.1998 t/m 31.08.1998), the Louisiana museum in Denmark and at the Hayward Gallery in London. Reduced versions have been on show at PS1 in New York (18.10.1998) and Bangkok.
Engels
Fins
kunstcatalogus
Keywords: Azië